Effect of drainage ratio during strawberry cultivation:The volatilomics-based shelf-life indicators for strawberry fruit - Cho, Jwa Yeong; Ryu, Da Hye; Hamayun, Muhammad; Park, Soo Hyun; Kim, Ho-Youn (Frontiers in Plant Science, 2023)
The metabolome of strawberries at harvest determines their storage capacity. Therefore, dynamics of volatile production during storage of strawberry cultivated under diverse drainage ratios, T1 (12.0%), T2 (25.3%), T3 (36.4%), and T4 (56.5%), were evaluated. Among the various non-target VOCs analysis, there were some groups including aldehydes, esters, and furans occupied over 5% with exhibiting high coefficient of determination (R2) following the days after storage (DAS). Aldehydes content decreased over the storage period, while the esters (methyl butanoate, methyl hexanoate, ethyl hexanoate, and benzyl acetate) and furanones (furaneol and mesifuran) were increased as representing aroma compounds in strawberry ripening. Even on the same day, it was investigated that the release of VOCs linked to fruit decay was delayed in the groups (T1 and T2) that were given relatively little water compared to T3 and T4. The hexanal and ethyl hexanoate as an over-ripened signal showed a rapid increase from 4 DAS to 5 DAS in T3 and T4, respectively, while T1 and T2 showed significant increase from 5 DAS to 6 DAS. Relatively slower over-ripening tendency of T1 and T2 was supported by changes of firmness, total soluble solid content, anthocyanin content, and antioxidant activity during storage. T1 and T2 showed higher antioxidant activity at the harvest time and lower anthocyanin accumulation than T3 and T4. The present study elucidated that the preharvest drainage changes during cultivation was involved in fruit quality during strawberry storage. Besides, volatilomics analysis depicted that T2 as an optimal ratio, could delay the occurrence of stress and senescence, and guaranteed the strawberry yield. In conclusion, this study provided evidence that the practical application of drainage ratios could improve horticultural product quality even with low water use and VOCs might be considered an early indicator for strawberry fruit shelf-life.